Comparative assessment of the accuracy of maximum likelihood and correlated signal enhancement algorithm positioning methods in gamma camera with large square photomultiplier tubes - Behnoosh Teimourian Fard; Mojtaba Shamsaei Zafarghandi (Majallahī-i pizishk-i hastahī Īrān, 2019)
Introduction: The gamma cameras, based on scintillation crystal followed by an array of photomultiplier tubes (PMTs), play a crucial role in nuclear medicine. The use of square PMTs provides the minimum dead zones in the camera. The camera with square PMTs also reduces the number of PMTs relative to the detection area. Introduction of a positioning algorithm to improve the spatial resolution in the detector with square PMT have been of interest in recent years. Methods: In this study, the maximum-likelihood and correlated signal enhancement positioning methods were implemented in a camera with square PMTs. The developed camera consists of 3/8” thick monolithic NaI(Tl) crystal coupled to the array of 76mm sized PMTs. The comparison is based on measuring full width at half maximum (FWHM) and standard deviation of FWHM of point sources in a 15×15 grid of samples with 2-mm grid spacing, produced using MLE and CSE positioning methods. Results:The intrinsic spatial resolution in (x, y) directions was (3.8, 3.8), (4.3, 4.5) mm for CSE and MLE methods respectively. Also, the standard deviations was almost the same in both methods (0.5 and 0.6 for CSE and MLE respectively). Although by applying MLE method, the resolution degrades by 16% but the produced image introduced acceptable quality. Conclusion: The results show the MLE method presented acceptable performance in comparison to CSE method as reference in the detector with large square PMTs. Note that the MLE method does not require any linearity correction process because it can estimate the exact position of events.